Beatitudes in Juvencus’ Epic "Evangeliorum libri quattuor" – Philologically Analyzed and Poetically Translated - Viktor Wintner (Vox Patrum, 2023)
Gaius Vettius Aquilinus Iuvencus is the author of the first biblical epic which is known as Evangeliorum libri quattuor. It retells the Gospel story in classical hexameter in order to adapt its form to the literary aesthetics of the 4th century pagan society. Through the analysis of his poetic version of the beatitudes, this study aims to uncover and appraise the basic principles of his periphrastic technique, whether they apply to the form or content of the Matthean original. It shows that the author constantly tries to vary its syntax with the intention to disturb its monotonous regularity. He also promotes the value of heavenly rewards promised to Christians, providing them with sympathetic epithets and embellishes the original with stylistic figures such as alliteration or contrast. As for the content, the most significant change is the occasional insertion of author’s comments, the purpose of which is to provide the Matthean text with additional theological information that he might find missing. The study concludes with our free translation of this passage into iambic heptameter or fourteener.